Estrategias metodológicas utilizadas por docentes que atienden niñas y niños preescolares de 2 a 4 años de edad - Bertha Barrantes-Alpízar; Éricka Corrales-Torres; Viviana González-Rodríguez; Zulay Pereira-Pérez; Eilyn Rodríguez-Fallas (Revista Electrónica Educare)
There were analyzed by means of 120 observations of classroom; the strategies that the teachers use to attend kids of 2 to 4 years of age. The main conclusion; indicates that a breach exists, between which the educators say that they do and what really they show in its professional exercise.